Prevalence and factors associated with sexual activities among high school students in Kendal regency of Indonesia - Fauzi, Ekha Rifki; Xenos, Peter; Cheumchit, Montakarn (Journal of Health Research, 2018)
Purpose - Sexual activities are a part of reproductive health risk indicator. The risk among adolescents is high globally. Unwanted pregnancy, the early sexual debut, inconsistent of condom use, sexually transmitted infection, and HIV are still the big problem in young people and drug & alcohol user include in the risks. These problems are significantly occuring in teenagers. The low of knowledge about the effect of these negative attitudes have been identified as factors where increase the opportunities of youth engaged in risk of sexual behaviors. The aim of this study was conducted to examine the prevalence and factor associated with sexual activities among high school students. Design/methodology/approach - A cross-sectional study was conducted among 145 male students and 315 female students. A multistage random sampling technique was used to select 460 students. A self-reported questionnaire was used including Illustrative Questionnaire for Interview-Surveys with Young People, Sexual Activity Scale and Sex Education Inventory, adopted in according to Indonesian context. Descriptive statistics, Chi-square test, and multivariate logistic regression were used to analyze the data. Findings - The prevalence and factors associated with sexual activities were separated in 4 groups to be 60.8% of male students, 21.4% of female students, 32.9% of rural area, and 35.2% of urban area. Factor associated with sexual activities were pornography p<0.001, substance use p<0.001, and smoking p<0.001, accessed sexual activities by internet p<0.001. The multivariate analysis, pornography [OR: 7.50, 95% CI = 2.50-22.50], knowledge of reproductive health [OR: 6.49, 95% CI= 2.29-18.35], substance use [OR: 2.67, 95% CI= 1.02-6.97) were significant factor associated with sexual activities among adolescents. Originality/value - The study found several factors associated with sexual activities among youth. These findings could become to aid the comprehensive sexual and HIV-AIDS education programs where are extremely needed for adolescents. There are need to provide some learning services in schools and community including health clinics for adolescent to increase knowledge of reproductive health and to reduce negative attitude of sexual activities.